Bioluminescent Human Thyrospheres Allow Noninvasive Detection of Anaplastic Thyroid Cancer Growth and Metastases In Vivo - Reeb, Ashley N. (Mary Ann Liebert, Inc., 2014)
Background: We have previously demonstrated that thyrospheres derived from human anaplastic thyroid cancer (ATC) cell lines can reconstitute and sustain tumor growth in vivo. The aim of this study was to use luciferase-expressing thyrospheres to establish a clinically relevant mouse model of ATC that allows noninvasive and sensitive monitoring of tumor progression. Methods: Two human ATC cell lines stably transfected with a firefly luciferase gene were used to generate thyrospheres under stem cell culture conditions. Cells were orthotopically implanted into the thyroids of immunodeficient NOD/SCIDIl2rg-/- mice to initiate tumors. Tumor progression and metastasis were evaluated by bioluminescent imaging weekly as well as histologic analysis postmortem. Results: We show that only 100 thyrosphere cells are needed for tumor development, and that tumors can be monitored with bioluminescent imaging as early as 7–14 days after implantation. Subsequent histologic evaluation of tissue sections confirmed characteristics of high-grade malignant neoplasms. Conclusions: This approach offers rapid and highly sensitive noninvasive detection options for the preclinical assessment of novel ATC therapeutics in vivo.